2021
DOI: 10.14503/thij-20-7356
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Treatment of Acute Myocardial Infarction With Ventricular Septal Rupture Due to Patient Fear During the COVID-19 Pandemic

Abstract: During the coronavirus disease 2019 (COVID-19) pandmic, more patients are presenting with complications late after acute myocardial infarction. We report the case of a 71-year-old man who delayed seeking medical care for 2 weeks, despite progressive shortness of breath, cough, and tactile fever, for fear of contracting COVID-19 in the hospital. Clinical and echocardiographic evaluation revealed a ventricular septal rupture secondary to acute myocardial infarction. The patient underwent urgent cardiac catheteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Another systematic review found similar results with a decline in other acute cardiac conditions, including acute coronary syndromes by as much as 50% [47]. The repercussions of these delays and declines are an increase in out of hospital death and more advanced presentations of cardiovascular disease [48,49]. The long-term sequelae of these advanced cardiovascular disease cases may be realized in the years to come.…”
Section: Access To Preventive Care and Care Utilizationmentioning
confidence: 72%
“…Another systematic review found similar results with a decline in other acute cardiac conditions, including acute coronary syndromes by as much as 50% [47]. The repercussions of these delays and declines are an increase in out of hospital death and more advanced presentations of cardiovascular disease [48,49]. The long-term sequelae of these advanced cardiovascular disease cases may be realized in the years to come.…”
Section: Access To Preventive Care and Care Utilizationmentioning
confidence: 72%
“…Clinical and echocardiographic recognition of VSR coinciding with electrocardiographic recognition of STEMI ( Table 1 ). In this category there were 42 cases [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ] (28 males) of mean age 67. The period of pre-hospital delay ranged from 6 h to 3 months.…”
Section: Resultsmentioning
confidence: 99%
“…The period of pre-hospital delay ranged from 6 h to 3 months. Twelve cases had a pre-hospital delay of 7 days or more [ [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ].…”
Section: Resultsmentioning
confidence: 99%